2019
DOI: 10.1111/ele.13202
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 does not stimulate carbon sink in a semi-arid grassland

Abstract: Elevated CO2 is widely accepted to enhance terrestrial carbon sink, especially in arid and semi‐arid regions. However, great uncertainties exist for the CO2 fertilisation effects, particularly when its interactions with other global change factors are considered. A four‐factor (CO2, temperature, precipitation and nitrogen) experiment revealed that elevated CO2 did not affect either gross ecosystem productivity or ecosystem respiration, and consequently resulted in no changes of net ecosystem productivity in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…2h; Q B = 5.70, P = 0.02). Similar to the observed increases in gross ecosystem productivity, ecosystem and soil respiration were also enhanced under eCO 2 , indicating that eCO 2 accelerates ecosystem carbon turnover through belowground processes (for example, microbial decomposition and soil CO 2 efflux) [49][50][51] . Root exudation and possibly root litter and organic matter decomposition might be stimulated under eCO 2 , thus a considerable fraction of increased net primary productivity is in fast-turnover pools that do not lead to carbon sequestration but are released back to the atmosphere.…”
supporting
confidence: 66%
“…2h; Q B = 5.70, P = 0.02). Similar to the observed increases in gross ecosystem productivity, ecosystem and soil respiration were also enhanced under eCO 2 , indicating that eCO 2 accelerates ecosystem carbon turnover through belowground processes (for example, microbial decomposition and soil CO 2 efflux) [49][50][51] . Root exudation and possibly root litter and organic matter decomposition might be stimulated under eCO 2 , thus a considerable fraction of increased net primary productivity is in fast-turnover pools that do not lead to carbon sequestration but are released back to the atmosphere.…”
supporting
confidence: 66%
“…Similarly, a recent study reported that N deposition can increase the sensitivity of plants to climatic changes such as attendant drought (Hess et al, ). Moreover, a water deficit can result in the allocation of more plant N to sink organs such as root systems (Xu, Zhou, & Wang, ) and result in a decrease in soil available N through plants absorption (Yuan et al, ); in contrast, enhanced precipitation might easily result in N consumption in drylands (Ren et al, ; Song et al, ). In a grassland ecosystem in New Zealand, an accelerated N‐cycling process was observed with increased precipitation, promoting plant community functioning (de Klein, Shepherd, & van der Weerden, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a water deficit can result in the allocation of more plant N to sink organs such as root systems (Xu, Zhou, & Wang, 2007) and result in a decrease in soil available N through plants absorption (Yuan et al, 2006); in contrast, enhanced precipitation might easily result in N consumption in drylands (Ren et al, 2017;Song et al, 2019).…”
Section: Interactive Effect Of Precipitation Changes and Nitrogen Amentioning
confidence: 99%
See 2 more Smart Citations